Determination of the optimum dietary essential amino acid profile for growing phase of Nile tilapia by deletion method - Mansano, Cleber F.M.; do Nascimento, Thiago M.T. [UNESP]; Peres, Helena; Rodrigues, Fábio H.F. [UNESP]; Khan, Kifayat U. [UNESP]; Romaneli, Rafael S. [UNESP]; Sakomura, Nilva K. [UNESP]; Fernandes, João B.K. [UNESP] (Elsevier, 2020)
The present study aimed to determine the optimal ratios of essential amino acids (EAAs) for Nile tilapia (Oreochromis niloticus) juveniles (150–200 g) using the deletion method. A total of 880 Nile tilapia juveniles (158.78 ± 0.9 g) were randomly distributed among 44 tanks (20 fish per tank/replicate) of 1500-L capacity each. During the 53 days feeding trial, fish were fed with the respective diets and daily feed intake was regularly recorded. In order to prevent any feed wastage, the fish were hand-fed three times a day until apparent satiation. A balanced diet (BD) and other ten diets were formulated by the deletion method, where the BD diet was adjusted to result in a reduction of 45% of each tested EAA. A group of fish at the beginning and at the end of the experiment was euthanized for the determination of the carcass nitrogen (N) composition. Based on the results of the present study, the optimal balance of essential amino acids for Nile tilapia juveniles weighing 150 and 200 g (g 16 g−1 N) was estimated as, arginine 4.88, lysine 5.87, threonine 6.02, histidine 1.73, isoleucine 3.26, leucine 4.82, methionine 2.36, phenylalanine 3.66, valine 3.46 and tryptophan 0.87.
Keywords: Amino acid nutrition; Ideal EAA profile; Nitrogen retention; Oreochromis niloticus